CROSS-LINGUISTIC INFLUENCE IN ENGLISH LANGUAGE ACQUISITION - Marina V. Jajić Novogradec (Faculty of Philosophy, University of Novi Sad, City Library of Pančevo, 2014)
Learning two or more foreign languages as compulsory or optional subjects in schools has led to a growing interest in the cross-linguistic research of multilingual learners. The aim of the paper is to investigate this cross-linguistic phenomenon in the school context by focusing on multilingual learners of English as a third language. In the fi rst part of the paper, important aspects of cross-linguistic infl uence and third language acquisition will be discussed. We shall also take a look at earlier studies of cross-linguistic infl uence on third language acquisition with a focus on various factors they investigate. In the second part of the paper, we shall present the study, that is the results of 16 secondary school students during two writing tasks in the English language and describe the frequency, type and direction of cross-linguistic infl uence in the English language acquisition.